Addressing challenges in gaining informed consent for a research study investigating falls in people with intellectual disability - Ho, P.; Downs, Jennepher; Bulsara, C.; Patman, S.; Hill, Anne-Marie (Wiley-Blackwell Publishing Ltd., 2018)
Accessible Summary: People with intellectual disability do not often take part in research. When people with intellectual disability are thinking about taking part in research, it is important that they are given support to participate in the decision-making. This study describes how an informed consent process was developed for people with intellectual disability and how it is working in a current study. Background: People with intellectual disability encounter substantial healthcare discrepancies, yet are under-represented in research. While people with intellectual disability can make valuable contributions to research and consequently improve their quality of life, researchers encounter multiple challenges including them in research. One challenge is to support them in making an informed decision to participate in research. Therefore, the aim of this study was to describe and reflect on a consent procedure used while gaining informed consent, when recruiting potential participants into an ongoing study. Methods: A systematic and holistic consent procedure, underpinned by ethical guidelines, was developed and used alongside recommended strategies to engage people with intellectual disability in a research study. Results: Only three participants (7.5%) were deemed capable of consenting independently, while 37 participants (92.5%) required the support of a proxy. Of these 37 participants, 22 participated in the consent process, while 15 depended mainly on their caregiver to make decisions for them. Adapted communication strategies were found to facilitate a person who has an intellectual disability's participation in the consent procedure. The adapted written information sheets were of secondary importance. Conclusion: The consent procedure was a respectful means of determining a person's capacity to consent and indicating where there was a need for proxy consent. Appropriate communication strategies and the inclusion of familiar caregiver(s) were critical components for facilitating the person with an intellectual disability to participate in the consent procedure.